Comprehensive Comparison of Various Techniques for the Analysis of Elemental Distributions in Thin Films: Additional Techniques. (December 2015) - Abou-Ras, Daniel; Caballero, Raquel; Streeck, Cornelia; Beckhoff, Burkhard; In, Jung-Hwan; Jeong, Sungho
Abstract: In a recent publication by Abou-Ras et al., various techniques for the analysis of elemental distribution in thin films were compared, using the example of a 2- µ m thick Cu(In, Ga)Se2 thin film applied as an absorber material in a solar cell. The authors of this work found that similar relative Ga distributions perpendicular to the substrate across the Cu(In, Ga)Se2 thin film were determined by 18 different techniques, applied on samples from the same identical deposition run. Their spatial and depth resolutions, their measuring speeds, their availabilities, as well as their detection limits were discussed. The present work adds two further techniques to this comparison: laser-induced breakdown spectroscopy and grazing-incidence X-ray fluorescence analysis.